2013
DOI: 10.5194/hess-17-5079-2013
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of riparian forest and groundwater in the hillslope hydrology of Sudanian West Africa (northern Benin)

Abstract: Abstract. Forests are thought to play an important role in the regional dynamics of the West African monsoon, through their capacity to extract water from a permanent and deep groundwater table to the atmosphere even during the dry season. It should be the case for riparian forests too, as these streambank forests are key landscape elements in Sudanian West Africa. The interplay of riparian forest and groundwater in the local hydrodynamics was investigated, by quantifying their contribution to the water balanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 52 publications
2
42
0
Order By: Relevance
“…They showed that the partition of the available energy reached a constant regime during the wet season. Guyot et al (2009) provided evidence that dry season evapotranspiration was linked to water table discharge; this result was further supported by recent hydrological studies Séguis et al, 2011;Richard et al, 2013).…”
supporting
confidence: 73%
“…They showed that the partition of the available energy reached a constant regime during the wet season. Guyot et al (2009) provided evidence that dry season evapotranspiration was linked to water table discharge; this result was further supported by recent hydrological studies Séguis et al, 2011;Richard et al, 2013).…”
supporting
confidence: 73%
“…Mean annual reference evapotranspiration [Allen et al, 1998] [S eguis et al, 2011b]. During the wet season, once soils are wet enough, actual evapotranspiration is equal to reference evapotranspiration [Richard et al, 2013], with a constant evaporative fraction [Guyot et al, 2012;Mamadou et al, 2014]. No streamflow is observed during the dry season at the outlet of the Nalohou catchment, in the Ara River, or in the larger Donga (586 km 2 ) basin.…”
Section: Study Areamentioning
confidence: 99%
“…The S-shaped function (van Genuchten, 1987) was used to describe the water stress response as it has been widely used to represent the water stress response function of trees (Zhu et al, 2009 andRichard et al, 2013):…”
Section: Plant Water Uptakementioning
confidence: 99%
“…Water, including surface water, groundwater, and soil water, is vital for tree growth (Zhu et al, 2009 andRichard et al, 2013), with groundwater being an important source in arid regions as it is relatively constant and stable. Many trees in arid regions are reported to be groundwater-dependent (Bulter et al, 2007 andGribovszki et al, 2010) and they can obtain large amounts of groundwater for transpiration through deep roots, especially during dry seasons (David et al, 2007 andLubczynski, 2009).…”
Section: Introductionmentioning
confidence: 99%